Pharmacokinetic modeling of intra-arterial nimodipine therapy for subarachnoid hemorrhage-related cerebral vasospasm - Seker, Fatih; Hesser, Jürgen; Neumaier-Probst, Eva; Groden, Christoph; Schubert, Rudolf (Clinical neuroradiology, 2017)
PurposeIntra-arterial (IA) administration of nimodipine has been shown to be an effective treatment for subarachnoid hemorrhage-related cerebral vasospasm. The concentrations achieved in cerebral arteries during this procedure, though, are unknown. Therefore, there are no clinical studies investigating dose-dependent effects of nimodipine. We aimed at providing a pharmacokinetic model for IA nimodipine therapy for this purpose.MethodsA two-compartment pharmacokinetic model for intravenous nimodipine therapy was modified and used to assess cerebral arterial nimodipine concentration during IA nimodipine infusion into the internal carotid artery (ICA).ResultsAccording to our simulations, continuous IA nimodipine infusion at 2 mg/h and 1 mg/h resulted in steady-state cerebral arterial concentrations of about 200 ng/ml and 100 ng/ml assuming an ICA blood flow of 200 ml/min and a clearance of 70 l/h. About 85 % of the maximal concentration is achieved within the first minute of IA infusion independent on the infusion dose. Within the range of physiological and pharmacokinetic data available in the literature, ICA blood flow has more impact on cerebral arterial concentration than nimodipine clearance.ConclusionThe presented pharmacokinetic model is suitable for estimations of cerebral arterial nimodipine concentration during IA infusion. It may, for instance, assist in dose-dependent analyses of angiographic results.
Published online: 8 September 2015
Gesehen am 03.07.2018